Family Resilience in Teenage Marriage in Cijambu Village, Tanjungsari District, Sumedang Regency - Gilang Septian; Jalaludin Jalaludin; Turasih Turasih (UIN Siber Syekh Nurjati Cirebon, 2025)
Early-age marriage remains a prevalent social phenomenon in rural areas and takes place within diverse social, economic, and cultural contexts. Rather than being understood solely as a practice with negative consequences, early-age marriage needs to be examined from the perspective of marital readiness and family resilience. This study aims to analyze the level of family resilience among early-age marriages in Cijambu Village, Tanjungsari District, Sumedang Regency by applying a family resilience framework encompassing legal and family integrity, physical resilience, economic resilience, social-psychological resilience, and socio-cultural resilience. This study employed a descriptive quantitative method involving 30 families who entered marriage during adolescence. Data were collected through questionnaires and analyzed using descriptive percentage techniques. The findings indicate that the level of family resilience among early-age marriages in Cijambu Village falls into the very high category, with an index score of 84%. Social-psychological resilience emerged as the strongest dimension, while physical resilience was the weakest. These findings suggest that family resilience in early-age marriage is contextual in nature and shaped by marital readiness as well as social and socio-cultural support within rural communities